A intervenção sanitária moderna e a quebra da confiança social sobre o risco: atores e pressupostos técnicos e políticos envolvidos na experiência de criação do modelo regulatório paraibano - Peixoto Neto, João (2011)
This monograph is a overview discussion of the political situation of Paraíba s brazilian state in which the first Paraíba s State Health Surveillance Agency (in portuguese Agência Estadual de Vigilância Sanitária - AGEVISA-PB) was created in 2002, specially all the decision process involved in the implementation of it s Public Health. The main points studied were the decisions, the governors agents, politicians and others interested persons involved on this process. Were highlighted during this study the participation of all agents involved in the early negociation, their interests, as well as their conflicting and cooperanting relationship, the strategies to induce the decisions and the rules that had effect on the action to be made, including the relation among the Executive and Legislative powers, on the State and Federal scope. This study was conducted between the year 2001 e 2002 and followed the influence of the first State Conference of Health Surveilance related to the changes that turned the State Coordination Health Surveillance to Paraíba s State Health Surveillance Agency, besides all the Public Health problems in that age. In this context, we emphasize the discussion about the Health Surveillance and contemporary risk society, as well all the alternatives that could be possible to the State Coordination Health Surveillance to become a agency and meet the demands of the healthcare and economic scenario and political situation of the state. As a consequence, we report the technical and political ways that were followed in the institutional transformation, whose design will be defined by complex processes of negotiation and consensus. The research was funded in large documentary material and interviews with key actors, which allowed empirically unravel the power relations that in a short time, led to the creation of the Paraíba s State Health Surveillance Agency (AGEVISA-PB). As such, it constituted itself as a political-institutional improvement, the first steps toward the discussions and reflections on its implementation, that this work proposes to introduce.